Long-term trends in the chemical and mechanical denudation in a small Carpathian catchment - Kijowska-Strugała, Małgorzata; Bochenek, Witold; Wójcik, Sabina (Quaestiones Geographicae, 2025)
Chemical and mechanical denudation are among the most important morphogenetic processes, especially in mountainous areas. The main objective of this study was to calculate the chemical deposition in precipitation as well as the chemical and mechanical deposition in a Carpathian stream between 1995 and 2023. The chemical denudation balance was also determined. Concentrations of several ions, including Cl−, S–SO 2−, N–NO −, P–PO 3−, N–NH +, Ca2+, Mg2+, Na+, K+ and HCO −, in precipitation and stream water were measured using ion chromatography, while suspended sediment during floods was measured using the 1 L bottle method. A significant increase in air temperature (+0.7°C per decade), especially during winter, led to a significant decrease in snowfall (SF) (−29.1 mm per decade) and snow cover duration (−16 days per decade), resulting in altered seasonal runoff patterns and an increase in the duration of hydrological drought. Decreases in ion concentrations and a 23% reduction in chemical denudation over the last decade highlight the effect of reduced anthropogenic pressures. Nutrient loads have also decreased by 38% due to improved wastewater management and agricultural abandonment, which has also resulted in a 60% reduction in suspended sediment loads. Mechanical denudation remains strongly linked to extreme hydrometeorological events.